TIMP3 overexpression in myeloid lineage alleviates pancreatic damage and confers resistance to the development of type 1 diabetes in the MLDS -induced model - Casagrande, Viviana; Menini, Stefano; Internò, Chiara; Pugliese, Giuseppe; Federici, Massimo; Menghini, Rossella (Frontiers in Endocrinology, 2024)
Type 1 diabetes mellitus (T1DM) development involves a complex interplay of genetic, environmental, and immunological factors. By modulating the activity of proteases and receptors, the protein tissue inhibitor of metalloproteinase 3 (TIMP3) plays a role in limiting the expression and function of pro-inflammatory cytokines, which have been implicated in the advancement of T1DM.This study was aimed at examining the effect of TIMP3 overexpression in myeloid cells on the development of T1DM. Twelve weeks after multiple low doses of streptozotocin (MLDS) treatment, diabetic mice overexpressing TIMP3 specifically in myeloid cells under the CD68 promoter (MacT3 mice) showed improved insulin secretion, islet morphology and vascularization, antioxidant defense system, and regulatory factors of mitochondrial biosynthesis and function. To get mechanistic insights into the origin of this protection, the severity of insulitis and inflammatory parameters were evaluated in pancreatic tissues 11 days after MLSD treatment, showing significantly reduced insulitis and levels of the pro-inflammatory cytokine tumor necrosis factor-α, interleukin -1β, and interferon -γ in MacT3 mice. In conclusion, the results indicate that TIMP3 is involved in maintaining islet architecture and functions, at least in part, through modulation of pro-inflammatory cytokine production associated with insulitis and may represent a novel therapeutic strategy for T1DM.